Comparison between Biosynthesis of ent-Kaurene in Germinating Tomato Seeds and Cell Suspension Cultures of Tomato and Tobacco - Yafin, Yitshak (1975)
Biosynthesis of ent-kaurene was investigated in extracts of cell suspension cultures derived from tobacco callus (Nicotiana tabacum L.), tomato callus (Solanum lycopersicum L.), and in germinating tomato seeds. Incubation of extracts derived from the two cell cultures with either isopentenyl pyrophosphate-(14)C or with (14)C-labeled mevalonate, followed by alkaline phosphatase hydrolysis, resulted in the formation of trans-geranylgeraniol-(14)C and trans-farnesol-(14)C. The corresponding pyrophosphates of trans-geranyl-geraniol-(14)C and trans-farnesol-(14)C were also detected. No detectable amount of ent-kaurene-(14)C was produced by these enzymatic preparations when trans-geranylgeranyl-(14)C pyrophosphate served as substrate. However, copalyl-(14)C pyrophosphate served as a substrate for the production of ent-kaurene. Cell-free extracts derived from germinating tomato seeds catalyzed the formation of ent-kaurene-(14)C from mevalonate-(14)C, isopentenyl-(14)C pyrophosphate, trans-geranylgeranyl-(14)C pyrophosphate, and copalyl-(14)C pyrophosphate.